Global landscape of renewable energy finance, 2023 (International Renewable Energy Agency, 2023)
Global investment in energy transition technologies, including energy efficiency, reached a record high of USD 1.3 trillion in 2022. However, annual investments need to at least quadruple to remain on track to achieve the 1.5°C Scenario in IRENA's World Energy Transitions Outlook 2023. Investment in renewable energy was also unprecedented - at USD 0.5 trillion - but represented less than one third of the average investment needed each year. Investments are also not flowing at the pace or scale needed to accelerate progress towards universal energy access; investments in off-grid renewable energy solutions in 2021 - at USD 0.5 billion - fell far short of the USD 2.3 billion needed annually in off-grid solar products alone (not including mini-grids). This Third Edition of the biannual joint report by the International Renewable Energy Agency (IRENA) and Climate Policy Initiative (CPI) analyses investment trends by technology, sector, region, source of finance and financial instrument in the period 2013-2020 and provides preliminary data for 2021-2022.